Drag Reduction of Anisotropic Superhydrophobic Surfaces Prepared by Laser Etching - Tuo, Yanjing; Zhang, Haifeng; Rong, Wanting; Jiang, Shuyue; Chen, Weiping; Liu, Xiaowei (Langmuir, 2019)
In this research, the anisotropic superhydrophobic surface is prepared on a stainless steel surface by laser etching, and the drag reduction property of the anisotropic surface is studied by a self-designed solid–liquid interface friction test device. Periodic arrangement structures of quadrate scales with oblique grooves are obtained on a stainless steel surface by a laser. After modification by fluoride, the surface shows superhydrophobicity and anisotropic adhesive property. Here, the inclined direction of grooves and the inverse direction are defined as RO and OR, respectively. By changing the inclination of the grooves, a surface is obtained with a contact angle of 160° and a rolling angle difference of 6° along the RO and inverse RO direction. It is verified by numerical simulation and experiment that the subjected force of water droplets on the surface is different along the RO and inverse RO direction. Furthermore, the as-prepared surface has different drag reduction effects along the two directions. With the increase of velocity, the drag reduction effect of the superhydrophobic surface decreases against the RO direction, while the drag reduction effect along the RO direction is almost unchanged. We believe the anisotropic surface will be helpful in novel microfluid devices and shipping transportation.